Cholesterol Assimilation of Saccharomyces cerevisiae B-18 isolated from gastrointestinal tract of Javanese duck - Istiqomah, L.; Anwar, M.; Anggraeni, A.S.; Damayanti, E. (Journal of the Indonesian Tropical Animal Agriculture, 2018)
This study had a purpose of obtaining potential indigenous yeasts for assimilating cholesterol and assessed the in vitro activity of Bile Salt Hydrolase (BSH) using Chloramphenicol Yeast Glucose (CYG) media supplemented CaCl2 and Taurodeoxycholic Acid (TDCA). Yeasts were collected from the gastrointestinal tract of Indonesian native chicken (Gallus javanicus), Javanese duck (Anas javanicus), and Muscovy duck (Anas moschata). The BSH assay was performed to determine secretion of BSH from yeast strain to conjugate bile salts into cholic acid-free by measuring precipitation zone in a specific medium. The quantitative measurement to assimilate cholesterol in yeast using CYG broth contained soluble cholesterol (500 ppm) and incubated at 30°C for 72 hours. Microplate reader used to analyze cholesterol content in the supernatant. Data were analyzed using Analysis of Variance (ANOVA) with one way completely randomized. Precipitation zone found among isolates did not significantly different (P>0.05). Isolate B-18 from Javanese duck performed the highest percentage of assimilating cholesterol with the value of 51.83% and identified as S. cerevisiae. This isolate was closely related to S. cerevisiae mt 21s (accession number X00149.1)based on phylogenetic tree analysis. It could be concluded that S. cerevisiae B-18was potential for assimilating cholesterol in vitro.